2017
DOI: 10.1016/j.jjcc.2016.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of safety and efficacy of periprocedural use of rivaroxaban and apixaban in catheter ablation for atrial fibrillation

Abstract: The incidence of asymptomatic cerebral microthromboembolism and hemopericardium in AF ablation is similar among the periprocedural use of rivaroxaban, apixaban, and warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…The process of the systematic literature search, screening, and selection is described in the PRISMA flow chart (Figure 1); 1757 records were identified by primary searches using pre‐specified keywords, and 984 duplicate records were removed. After excluding 749 records based on the abstract/title and another 15 records after detailed article screening, six RCTs 20‐25 and three POSs 26‐28 published between 2016 and 2019 were included in the meta‐analyses. The nine studies included 2578 patients, and 55% (1410/2578) of these patients received MI‐NOAC with up to two doses withheld before AF ablation.…”
Section: Resultsmentioning
confidence: 99%
“…The process of the systematic literature search, screening, and selection is described in the PRISMA flow chart (Figure 1); 1757 records were identified by primary searches using pre‐specified keywords, and 984 duplicate records were removed. After excluding 749 records based on the abstract/title and another 15 records after detailed article screening, six RCTs 20‐25 and three POSs 26‐28 published between 2016 and 2019 were included in the meta‐analyses. The nine studies included 2578 patients, and 55% (1410/2578) of these patients received MI‐NOAC with up to two doses withheld before AF ablation.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 42 were excluded as they did not meet the inclusion criteria (7 reviews and meta-analysis; 7 papers without outcomes of OACs; 9 papers without separate information on apixaban or rivaroxaban or dabigatran or edoxaban; 12 studies with duplicate data, 1 on the setting of direct current cardioversion and 7 with mixed diseases except for AF). Finally, 30 studies were included, 11 of which were studies on specific settings of RFA 9,[11][12][13][14][15][16][17][18][19][20] . The selection process is shown in…”
Section: Resultsmentioning
confidence: 99%
“…Dillier et al 18 used phenprocoumon as VKA, whereas warfarin was used in all other studies. The target international normalized ratio (INR) in the VKA group was 2.0-3.0 in all studies, except for patients in Yoshimura et al 13 (target INR not reported) and patients aged 70 years and older in Nagao et al 22 (target INR 1.6-2.6).…”
Section: Study Selection and Characteristicsmentioning
confidence: 90%
“…More recently, numerous studies were published, including additional randomized data that may strengthen the power of pooled outcomes. [10][11][12][13] Therefore, we aimed to perform an updated systematic review and meta-analysis to investigate the efficacy and safety of NOACs vs VKAs for uninterrupted OAC in patients with AF undergoing catheter ablation.…”
Section: Introductionmentioning
confidence: 99%